2010
DOI: 10.1007/s00464-010-1047-5
|View full text |Cite
|
Sign up to set email alerts
|

Staple line reinforcement in laparoscopic bariatric surgery: does it actually make a difference? A systematic review and meta-analysis

Abstract: Although several drawbacks exist, this study illustrates two important aspects: that current staplers may not be uniformly reliable, and that staple line reinforcement does not seem to have any clear benefit, at least concerning leak rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 24 publications
0
21
0
1
Order By: Relevance
“…Three meta-analyses and several systematic reviews have been published within the past 5 years on the use of staple line reinforcement with varying conclusions ranging from no significant effect on bleeding or leak, variable effect on leak depending on the material used for buttressing without assessment of bleeding and no effect on leak but decreased staple line bleeding. One review identified buttressing to be associated with an increased risk of bleeding [67][68][69][70][71][72][73][74][75][76]. There is one randomized controlled trial on the use of fibrin sealant during SG that reported a significant reduction in operative bleeding, although the clinical relevancy of this finding was not clear.…”
Section: Prevention Of Gi Leaks After Sgmentioning
confidence: 98%
“…Three meta-analyses and several systematic reviews have been published within the past 5 years on the use of staple line reinforcement with varying conclusions ranging from no significant effect on bleeding or leak, variable effect on leak depending on the material used for buttressing without assessment of bleeding and no effect on leak but decreased staple line bleeding. One review identified buttressing to be associated with an increased risk of bleeding [67][68][69][70][71][72][73][74][75][76]. There is one randomized controlled trial on the use of fibrin sealant during SG that reported a significant reduction in operative bleeding, although the clinical relevancy of this finding was not clear.…”
Section: Prevention Of Gi Leaks After Sgmentioning
confidence: 98%
“…Gastric leaks after secondary LSG are risks that must be considered in the management of bariatric patients. One surgical team has suggested reinforcing the staple line by buttressing the staple line with an absorbable polymer membrane [15] to prevent leaks by staple line disruption; others have contested their efficiency [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…As for clinical aspects, a systematic review by Giannopoulos et al 15 showed no difference in regard of the staple line rupture in patients undergoing laparoscopic bariatric surgery with and without reinforcement 15 . Dapri et al 8 randomized patients undergoing vertical gastrectomy in groups with clipping, suture reinforcement and Seamguard® (WL Gore & Associates, Inc, Flagstaff, AZ).…”
Section: Discussionmentioning
confidence: 99%